2005
DOI: 10.1007/s10152-005-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Shoot organization in the seagrass zostera noltii: implications for space occupation and plant architecture

Abstract: The growth pattern of the seagrass Zostera noltii is described through the analysis of the shoot primordium organization within different shoot types using optical and scanning electron microscopy. Both histological approaches showed that Z. noltii shoots are organized by a successive repetition of a unit named ''phytomer'' (shoot primordium, node, internode, root, sheath and leaf), in resemblance with the shoot structure described for land grasses. This study showed that differences among shoot types are dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Its ribbon-shaped leaves are 0.5-1.5 mm wide and 6-22 cm long [Phillips and Meñez, 1988] and above ground biomass shows a strong seasonality of high values in summer and low values in winter [Curiel et al, 1996]. Shoots grow from a rhizome system which builds a dense mesh by branching in almost every node [Brun et al, 2006]. The root/rhizome system is located approximately 3-5 cm below the sediment surface [Duarte et al, 1998] and its biomass remains constant throughout the year [Pergent-Martini et al, 2005].…”
Section: Study Sitementioning
confidence: 99%
“…Its ribbon-shaped leaves are 0.5-1.5 mm wide and 6-22 cm long [Phillips and Meñez, 1988] and above ground biomass shows a strong seasonality of high values in summer and low values in winter [Curiel et al, 1996]. Shoots grow from a rhizome system which builds a dense mesh by branching in almost every node [Brun et al, 2006]. The root/rhizome system is located approximately 3-5 cm below the sediment surface [Duarte et al, 1998] and its biomass remains constant throughout the year [Pergent-Martini et al, 2005].…”
Section: Study Sitementioning
confidence: 99%
“…2003) and Z. noltii is able to acclimate to different environmental conditions optimizing its space occupation strategy (Peralta et al. 2005; Brun et al. 2006; Cabaço et al.…”
Section: Introductionmentioning
confidence: 99%
“…Peralta et al (2005) reported physiological and morphological variations of Z. noltii plants in stable and recovering meadows, but the expected changes at higher organizational-levels, i.e., population-and community-levels, and its consequences to the adjacent coastal area were not investigated. Because seagrass meadows behave differently during the expansion ⁄ colonization process (Duarte & Sand-Jensen 1990a;Brun et al 2003) and Z. noltii is able to acclimate to different environmental conditions optimizing its space occupation strategy (Peralta et al 2005;Brun et al 2006;Cabaço et al 2009), we hypothesized that the population dynamics and production of the species would be different under different developmental stages of meadows. An area deeply affected by the artificial relocation of an inlet, which had a strong impact in local sedimentary and hydrodynamics (Dias et al 2009) and in seagrass landscape (Cunha et al 2005), being colonized by Z. noltii and an undisturbed, homogeneous Z. noltii meadow were investigated in Ria Formosa.…”
Section: Introductionmentioning
confidence: 99%
“…Clonality may be viewed as a simple way of growth, where plants are arranged by repetition of a fundamental unit, the phytomer (sensu Briske 1991 and Brun et al. 2006a ). Moreover, environmental variability can be somewhat managed throughout the large architectural and functional variability driven by clonal growth (Short 1983 ; Peralta et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, seagrass meadows are formed by the reiteration of small units, the clone, which is built by ramets and thus by the repetition of the simplest unit, the “phytomer” (Briske 1991 ; Brun et al. 2006a ). As it was recently expressed by Duarte et al.…”
Section: Introductionmentioning
confidence: 99%